2008
DOI: 10.1111/j.1365-3040.2008.01831.x
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid signalling when soil moisture is heterogeneous: decreased photoperiod sap flow from drying roots limits abscisic acid export to the shoots

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
115
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 30 publications
12
115
0
3
Order By: Relevance
“…In response to drying soil or a change in salinity, ABA levels in the stem xylem rise rapidly (Jeschke et al, 1997). Movement of ABA from the portion of the root system that senses the change in soil salinity or water availability to the leaves is important in the coordination of the plant response (Dodd et al, 2008(Dodd et al, , 2010Puértolas et al, 2015). In response, patterns of root growth are altered, with some root tips inhibited and others stimulated, and stomata in the leaf close (Daszkowska-Golec and Szarejko, 2013;Harris, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In response to drying soil or a change in salinity, ABA levels in the stem xylem rise rapidly (Jeschke et al, 1997). Movement of ABA from the portion of the root system that senses the change in soil salinity or water availability to the leaves is important in the coordination of the plant response (Dodd et al, 2008(Dodd et al, , 2010Puértolas et al, 2015). In response, patterns of root growth are altered, with some root tips inhibited and others stimulated, and stomata in the leaf close (Daszkowska-Golec and Szarejko, 2013;Harris, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was observed that the ABA concentration under PRD was higher than RDI in most measurements taken in our study. Accumulated evidence has indicated that, given the same irrigation volume, PRD frequently results in higher ABA concentration in the xylem than RDI, which has been considered to contribute to better stomatal control over plant water use [43,44] .…”
Section: Resultsmentioning
confidence: 99%
“…Detailed work by Dodd and colleagues (Dodd et al 2006(Dodd et al , 2008a(Dodd et al , 2008bDodd 2007) has shown how PRD can enhance hormone signalling between roots and shoots and that such signalling can have beneficial effects on the efficiency of water use. However, enhanced signalling does not always occur and this is particularly the case at lower soil water contents, an observation that can explain some of the negligible effects of PRD reported by Sadras.…”
mentioning
confidence: 99%